2017
DOI: 10.1016/j.biomaterials.2017.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Silk-based anisotropical 3D biotextiles for bone regeneration

Abstract: Bone loss in the craniofacial complex can been treated using several conventional therapeutic strategies that face many obstacles and limitations. In this work, novel three-dimensional (3D) biotextile architectures were developed as a possible strategy for flat bone regeneration applications. As a fully automated processing route, this strategy as potential to be easily industrialized. Silk fibroin (SF) yarns were processed into weft-knitted fabrics spaced by a monofilament of polyethylene terephthalate (PET).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…In natural cartilage tissue, the ECM provides a complex environment of physical, chemical and mechanical cues that directly affect and guide cell behavior. In the recent years, SF has demonstrated to be a robust natural material widely explored for bone [41], cartilage [27] and osteochondral [42] TE. Its processing versatility allowed to extend the use of SF for TE applications of ligament [43], blood vessels [44] or skin [45].…”
Section: Discussionmentioning
confidence: 99%
“…In natural cartilage tissue, the ECM provides a complex environment of physical, chemical and mechanical cues that directly affect and guide cell behavior. In the recent years, SF has demonstrated to be a robust natural material widely explored for bone [41], cartilage [27] and osteochondral [42] TE. Its processing versatility allowed to extend the use of SF for TE applications of ligament [43], blood vessels [44] or skin [45].…”
Section: Discussionmentioning
confidence: 99%
“…Silk‐based scaffolds presented good biological performance when seeded with hASCs. In a work performed by Ribeiro et al, SF biotextiles also showed good hASCs adhesion and proliferation, as well as the ability of these type of cells to differentiate in an osteogenic lineage.…”
mentioning
confidence: 99%
“…Silk is a natural fibrous polymer consisting of repetitive protein sequences and due to its characteristics such as elasticity, biocompatibility and biodegradability have applicability for bone regeneration [113][114][115]. Three different scaffolds: alginate, alginate/hydroxyapatite, and alginate/hydroxyapatite/silk fibroin were analyzed in an experiment [115].…”
Section: Polymer Biomaterialsmentioning
confidence: 99%